Effect of draw ratio and sheet thickness on earing and drawability of Al1200 cups (2010)
"The effect of blank/punch diameter ratio (draw ratio) in deep drawing on earing for different gauges of Al 1200 sheet was studied. Using 60, 62, 64 and 65mm diameter circle blanks and 33mm diameter punch die, fully annealed Al 1200 sheets of gauge thicknesses 0.6 to 2.0mm were subjected to deep drawing on an ErrichsenR cup drawing machine. The results showed that with increase in sheet thickness, the smaller is the draw ratio that would draw the sheet. For 0.6-0.9mm sheet thickness, cups were drawn with draw ratios of 60/33 to 65/33. For sheet thicknesses of 1.2-1.58mm, only 60/33 and 62/33 draw ratios were observe to draw cups. Earing was observed to generally increase with increasing draw ratio using the same sheet thickness. It was also observed that for thinner sheets (0.6-0.9mm), using the same draw ratio, earing increased with increasing sheet thickness. For thicker sheets (1.2-1.58mm) earing was observed to decrease with increasing sheet thickness. After that, there was an increase for deep-drawn 2mm thick sheet. Higher draw ratios were observed to draw deeper cup depths with minimal earing. The depth of jcups drawn with 65/33 draw ratio was observed to be about 28% more than those drawn with 60/33 draw ratio with an increase in earing of only 0.84% for 0.6mm thick sheet and 1.2% for 0.9mm thick sheets. Earing was also observed to increase by 1.64% for the 2mm thick sheet that had undergone grain growth over the fine grained one. "